Dessecação química e retardamento de colheita em soja visando à produção de sementes - Barbosa, Adriano Silveira (Universidade Federal do Tocantins, 2018)
The application of desiccants in pre-harvesting of soybeans contributes to the reduction of seed exposure to unfavorable climatic conditions and to reduce the possibility of germination and vigor losses, as well as to allow uniformity of maturation and to anticipate harvesting of soybean from three days to one week. However, studies on its effect on physiological quality and chemical composition of soybeans with harvest delay are scarce in crops under low latitude. Thus, in the agricultural year 2016/17, an experiment was carried out in Gurupi-TO, in a randomized block design, with three replications, and the treatments were arranged in a sub-split plot scheme, being allocated in plots two cultivars of soybeans with different growth types (NA 8015 RR-undetermined; M 8349 IPRO-determined), in the subplots two management systems (with and without desiccant application) and in sub-subplots four harvesting times (R8, R8+7, R8+14, R8+21). The desiccant used was the herbicide Gramoxone (active principle Paraquat), at the recommended dosage for soybean (1.5 L.ha-1), applied at the R7.2 stage of the culture. After the harvest, the seeds were submitted to germination tests in the laboratory, field emergence, yield, oil content and grain protein. The means of cultivars and management systems were compared by the Scott-Knott test, at 5% significance. For the harvest times, orthogonal polynomials were fitted. The cultivar M 8349 IPRO was more conducive to desiccation. Harvest delay negatively affected the physiological quality of the seeds, with no effect on the chemical composition of the seeds. Chemical desiccation kept the seeds with better physiological quality for a longer period.